"Este coronel é dotado de prudência, moderação e acolhimento”: Joaquim Xavier Curado e o governo da ilha de Santa Catarina (1800-1805) - Bonhemberger, Tiago Vinicius (2021)
The main objective of this dissertation is to analyze the government of Colonel Joaquim Xavier Curado on the island of Santa Catarina during the period from 1800 to 1805. For this, we used the correspondence exchanged by this official with the Portuguese administrative authorities hierarchically superior to him. During the study, we sought to understand how governability occurred in a territory subordinated to Rio de Janeiro, exemplifying how this type of agent serves and responds to the government. In the course of the work, we also tried to identify: the priorities of this military man's government; the most recurrent subjects in his communication; what were the mechanisms used by him to project himself to an administrative position, since Xavier Curado belonged to a social stratum less highly rated for government positions, he was born in conquests. Based on the analysis of these elements, we conclude that the government of Santa Catarina was not, for Joaquim Xavier Curado, a definitive milestone for his career, but a step in a path that led him to nobility. While governing the island of Santa Catarina, a strategic position for the maintenance of Portuguese domains in the American extreme south, the officer acted as expected, inserting himself in a certain model of reason of state implemented by the Portuguese Empire. In this way, Joaquim Xavier Curado becomes an exemplary governor, in the sense that in his government nothing out of the ordinary happened. Through the accumulation of experiences through mistakes and successes, he exercised the governing practice, and by operating within the established models, he ensured space for the continuation of his career.